METHODS FOR RHEUMATOID ARTHRITIS ACTIVITY SELF-ASSESSMENT: PROS AND CONS - E. V. Yurova; E. V. Lygina; G. G. Bagirova; S. S. Yakushin (Научно-практическая ревматология)
The paper analyzes the foreign and Russian literature devoted to teaching patients how to control rheumatoid arthritis (RA) disease activity. It shows the historical development of this matter. The paper also describes currently known methods for the self-assessment of RA disease activity. The factors that affect the correctness of both a patient's selfassessment and a rheumatologist's evaluation are indicated. The results of studies, which prove the practical importance of self-control of RA activity, are presented. The paper demonstrates the ambiguity of rheumatologists' opinions on whether self-control can be applied.